Glass: Home of the Periodic Table - Shakhgildyan, Georgiy; Lipatiev, Alexey; Lotarev, Sergey; Fedotov, Sergey; Sigaev, Vladimir (Frontiers in Chemistry, 2020)
Glass is the most common material around us, and humankind uses it every day for more than 5000 years. However, from the chemical point of view, glass is the only material that could represent almost all elements of the Periodic Table inside itself, showing the effect of the Periodic Law on properties of the final material. In this paper, we show the most remarkable examples demonstrating that glass can rightfully be called “home” for all chemical elements providing different properties depending on its composition. We gave a new look at the Periodic Table and described how a small number of glass-forming components creates unique glass structure which could enclose almost all remaining elements including transition and noble metals, lanthanides and actinides as modifying components providing an inconceivable number of discoveries in material science. Moreover, we reviewed a series of studies on the direct femtosecond laser writing in glasses which paves the way for a redistribution of chemical elements in the spatially confined nanosized zone in glass volume providing unique properties of laser-induced structures. Finally, for the first time, we reproduce the Periodic Table in birefringence colors in the bulk of silica glass using a direct laser writing technique. This image of 3.6x2.4 mm size can withstand temperature up to 900°C, humidity, electromagnetic fields, powerful cosmic and reactor radiation and other environmental factors and demonstrates both the art of direct laser writing and symbolic role of glass as the safest and eternal home for the Periodic Table.